Pemanenan Air untuk Menciptakan Sistem Usahatani yang Berkelanjutan (Pengalaman di Wonosari, Daerah Istlmewa Yogyakarta) - Nani Heryani; Gatot Irianto; Nurwindah Pujilestari (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2002)
Rainfall-runoff harvesting on upland farming system and its effect to water production function and farming system sustainability were discussed in this paper. Water production function indicated the exchange of the total rainfall to rainfall net. The result of the experiment showed that measurement of the upland productivity will be reached through: (I) minimum fluctuation of water availability, (2) maximum water storage capacity of natural or artificial watershed; (3) optimum water use efficiency and variability of commodity. Rainfall-runoff harvesting through modification of hydrology characteristics by building channel reservoir on the river stream retained water in the rainy season and will distribute water in the dry season. Key words: Wafer harvesting, Channel reservoir, Sustainable upland farming system